Influence of fertigation with wastewater on the soil and growth of tree seedlings (Research, Society and Development, 2022)
In Brazil, swine farming is a very important livestock activity in many ways, as it promotes the generation of employment and income in rural areas, but on the other hand, it is responsible for the production of large amounts of waste such as swine wastewater (SW). This study aimed to evaluate the quantitative changes in the main chemical attributes of the soil and in the morphometric characteristics of tree seedlings fertilized with different doses of swine wastewater (SW). The experiment was carried out in the environmental experimentation area of the Federal University of Paraná, Setor Palotina. The design used was in randomized blocks (RBC) where six treatments with different doses of SWW were tested, being: T1= 0 L m-2, T2= 1 L m-2, T3= 2 L m-2,T4= 3 L m-2, T5= 4 L m-2, T6= 5 L m-2 applied for fertilizing Citharexylum myrianthum Cham seedlings. The application of the residue resulted in an increase in the percentage of organic matter in the layer from 0 to 20 cm along with the levels of K+, Mn+2, Zn+, Cu+, CTC, saturation by Al+ 3 and e H+3+ Al+3 and decrease in pH, Ca+ 2, Mg+ 2 and base saturation levels. As for the growth of seedlings, the highest values of increments both in height and in diameter were identified in plants that received doses of 5 L m-2 of ARS.